Customer loyalty: A case study of Bank Rakyat, Melawati branch, Kuala Lumpur / Norsaliza Mohd Saad - Mohd Saad, Norsaliza (Faculty of Business and Management, 2006)
In a service business, quality depends on the customer's experience with delivery because, unlike products, services are experienced while they are produced. Studies from the service literature emphasize the importance of quality perceptions and the relationship between service satisfaction and quality toward customer loyalty. There is evidence to suggest that service quality leads to customer satisfaction and helps to keep existing customers and attract new ones. This project paper, describe a study designed to examine the most determinants of service quality. The study sample comprised 31 customers. A comprehensive frequency analysis was conducted to reveal the determinants of service quality. From the analysis, service product found to be most important determinants of selvice quality. It shown that, the most customers satisfied with the product service provide by Bank Rakyat. Customers associated with the decision making process for personal banking service and provide a rough measure of the effectiveness of the various bank's effort to market new product and services. From the study, researcher collect data from the customers of Bank Rakyat, Melawati branch, Kuala Lumpur.The data is analyzed and processed by using Statistical Package for Social Sciences (SPSS). Frequency table and correlation is used to analyze the data. Lastly, from the findings, conclusion and recommendations is made to improve the performance of Bank Rakyat, Melawati branch, Kuala Lumpur.